A Context-Specific and Dualistic Examination of Consumer Behaviour in the Context of Digital Products: The Case of Purchasing Digital Music from Music Download Stores in Finland - Makkonen, Markus (2019)
Although digital products have become an important part of the lives of many consumers, there are several gaps in our understanding of their consumption behaviour. In particular, there seems to be an urgent call for studies that exam-ine the phenomenon from a more context-specific and a dualistic perspective that focuses on both the enablers and inhibitors of information systems (IS) ac-ceptance and use. The objective of this thesis is to address this call. In doing so, the thesis argues to be able to promote not only the breadth and depth of the present theoretical understanding of consumer behaviour in the context of digi-tal products but also the relevance of the conducted research to practice. To evidence this argument, a case study is conducted, concentrating on the case context of consumer purchase behaviour in music download stores. The empir-ical data for the case study, which was collected from Finnish consumers in an interview study and two survey studies, is analysed in a mixed methods man-ner by using both qualitative and quantitative methods. The main findings of the thesis are two new theories for explaining consumer purchase behaviour in music download stores. Through these theories and its other findings, the the-sis demonstrates its ability to promote both the depth and breadth of the pre-sent theoretical understanding of consumer purchase behaviour in music download stores. This is manifested as three new rich theoretical insights con-cerning the pronounced role of existing practices and preferences, risk percep-tions, and the utilitarian versus hedonic dimension as antecedents of consumer purchase behaviour in music download stores. After discussing the generalisa-bility of its findings from the specific case context of digital music to the broad-er context of digital products as well as its contributions to IS research in gen-eral, the thesis also demonstrates how its more context-specific and dualistic perspective can promote the relevance of the conducted research to practice. To do this, the thesis proposes a four-step “recipe” of concrete managerial actions for promoting the adoption of music download stores and, potentially, of other types of stores and services that sell digital products. The thesis concludes with a brief discussion of its main limitations and potential paths for future research.